Acorn crop size and pre-dispersal predation determine inter-specific differences in the recruitment of co-occurring oaks. - Espelta, Josep Maria; Cortes, P.; Molowny-Horas, R.; Retana, J. (Oecologia, 2009)
The contribution of pre-dispersal seed predation to inter-specific differences in recruitment remains elusive. In species with no resistance mechanisms, differences in pre-dispersal predation may arise from differences in seed abundance (plant satiation) or in the ability of seeds to survive insect infestation (seed satiation). This study aimed to analyse the impact of pre-dispersal acorn predation by weevils in two co-occurring Mediterranean oaks (Quercus ilex and Quercus humilis) and to compare its relevance with other processes involved in recruitment. We monitored the patterns of acorn production and acorn infestation by weevils and we conducted experimental tests of acorn germination after weevil infestation, post-dispersal predation and seedling establishment in mixed forests. Monitoring and experimental data were integrated in a simulation model to test for the effects of pre-dispersal predation in recruitment. In both oaks pre-dispersal acorn infestation decreased with increasing acorn crop size (plant satiation). This benefited Q. ilex which exhibited stronger masting behaviour than Q. humilis, with almost a single and outstanding reproductive event in 6 years. Acorn infestation was more than twice as high in Q. humilis (47.0%) as in Q. ilex (20.0%) irrespective of the number of seeds produced by each species. Although germination of infested acorns (seed satiation) was higher in Q. humilis (60%) than in Q. ilex (21%), this could barely mitigate the higher infestation rate in the former species, to reduce seed loss. Conversely to pre-dispersal predation, no inter-specific differences were observed either in post-dispersal predation or seedling establishment. Our results indicate that pre-dispersal predation may contribute to differences in seed supply, and ultimately in recruitment, between co-existing oaks. Moreover, they suggest that seed satiation can barely offset differences in seed infestation rates. This serves as a warning against overemphasising seed satiation as a mechanism to overcome seed predation by insects.
The following values have no corresponding Zotero field: accession-num: 19544074
Keywords: Animals; Feeding Behavior; Feeding Behavior: physiology; germination; Germination: physiology; Models, Biological; Quercus; Quercus: physiology; Seeds; Seeds: growth & development; Spain; Species Specificity; weevils; Weevils: physiology

Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I.; Tomás-Barberán, Francisco a (Journal of Agricultural and Food Chemistry, 2007)
Ellagitannin-containing foods (strawberries, walnuts, pomegranate, raspberries, oak-aged wine, etc.) have attracted attention due to their cancer chemopreventive, cardioprotective, and antioxidant effects. Ellagitannins (ETs) are not absorbed as such but are metabolized by the intestinal flora to yield urolithins (hydroxydibenzopyran-6-one derivatives). In this study, Iberian pig is used as a model to clarify human ET metabolism. Pigs were fed either cereal fodder or acorns, a rich source of ETs. Plasma, urine, bile, lumen and intestinal tissues (jejunum and colon), feces, liver, kidney, heart, brain, lung, muscle, and subcutaneous fat tissue were analyzed. The results demonstrate that acorn ETs release ellagic acid (EA) in the jejunum, then the intestinal flora metabolizes EA sequentially to yield tetrahydroxy- (urolithin D), trihydroxy- (urolithin C), dihydroxy- (urolithin A), and monohydroxy- (urolithin B) dibenzopyran-6-one metabolites, which were absorbed preferentially when their lipophilicity increased. Thirty-one ET-derived metabolites were detected, including 25 urolithin and 6 EA derivatives. Twenty-six extensively conjugated metabolites were detected in bile, glucuronides and methyl glucuronides of EA and particularly urolithin A, C, and D derivatives, confirming a very active enterohepatic circulation. Urolithins A and B as well as dimethyl-EA-glucuronide were detected in peripheral plasma. The presence of EA metabolites in bile and in urine and its absence in intestinal tissues suggested its absorption in the stomach. Urolithin A was the only metabolite detected in feces and together with its glucuronide was the most abundant metabolite in urine. No metabolites accumulated in any organ analyzed. The whole metabolism of ETs is shown for the first time, confirming previous studies in humans and explaining the long persistency of urolithin metabolites in the body mediated by an active enterohepatic circulation.
From Duplicate 2 (Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco A)From Duplicate 2 (Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco A)The following values have no corresponding Zotero field: publisher: American Chemical Society accession-num: 17990850
Keywords: Animal; Animals; bile; bioavailability; Biological Availability; Body Fluids; Body Fluids: chemistry; Cereals; Cereals: chemistry; colon; diet; ellagic acid; Ellagitannin; gall bladder; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: metabolism; Hydrolyzable Tannins: pharmacokinetics; intestine; metabolism; Models; Quercus; Seeds; Seeds: chemistry; Swine; Swine: metabolism; Tissue Distribution; urolithin

Seed germination of Quercus robur, q. pyrenaica and q. ilex and the effects of smoke, heat, ash and charcoal - Reyes, Otilia; Casal, Mercedes (Ann. For. Sci., 2006)
This study is centred on Quercus robur, Q. pyrenaica and Q. ilex that have a distribution area covering all Europe. Fire is a frequent ecological factor in many ecosystems, especially in those with Mediterranean climates. Our working hypothesis is that fire affects the germination process. An experiment was carried out testing the following treatments: Control, Smoke-5 min, Smoke-10min, Smoke-15 min, 60 ºC-5 min, 60 °C-15 min, 90 ºC-5 min, 110 ºC-5 min, 150 ºC-5 min, Ash, Ash Dilution and Charcoal. The seed incubation was spread over a year. The germination rates of the Control are very high, especially in Q. ilex. Almost none of the treatments inhibit germination and only the Q. ilex seeds, when subjected to 150 ºC-5 min, show a marked inhibition. Q. robur and Q. pyrenaica take a year to complete their germination, while Q. ilex only takes 22 weeks. Probably, this reproductive behaviour is related to the climate characteristics to which the species have become adapted. Finally, fire does not determine the germination process, the recruitment of new individuals being independent of fire.
Keywords: fire; germination; Quercus; reproductive strategies; Seeds

Changes in pectins and MAPKs related to cell development during early microspore embryogenesis in Quercus suber L. - Ramírez, Carmen; Testillano, Pilar S.; Pintos, Beatriz; Moreno-Risueño, Miguel a; Bueno, María a; Risueño, María C. (European journal of cell biology, 2004)
The occurrence and significance of changes in cell wall components and signalling molecules has been investigated during early microspore embryogenesis in cork oak (Quercus suber L.) in relation to cell proliferation and cell differentiation. Microspore embryogenesis has been induced in in vitro anther cultures of Q. suber by the application of a stress treatment of 33 degrees C. After the treatment, microspores at the responsive developmental stage of vacuolate microspore switched towards proliferation and the embryogenesis pathway to further produce haploid plantlets. Ultrastructural and immunocytochemical analysis revealed changes in cell organisation after induction at different developmental stages, the cellular features displayed being in relation to the activation of proliferative activity and the beginning of differentiation in young and late proembryos. Immunogold labelling with JIM5 and JIM7 antibodies showed a different presence of pectin and level of its esterification in cell walls at different developmental stages. Non-esterified pectins were found in higher proportions in cells of late proembryos, suggesting that pectin de-esterification could be related to the beginning of differentiation. The presence and subcellular distribution of Erk 1/2 MAPK homologues have been investigated by immunoblotting, immunofluorescence and immunogold labelling. The results showed an increase in the expression of these proteins with a high presence in the nucleus, during early microspore proembryos development. The reported changes during early microspore embryogenesis are modulated in relation to proliferation and differentiation events. These findings provided new evidences for a role of MAPK signalling pathways in early microspore embryogenesis, specifically in proliferation, and would confer information for the cell fate and the direction of the cell development.
The following values have no corresponding Zotero field: accession-num: 15346811
Keywords: Cell Differentiation; Cell Differentiation: physiology; Electron; MAPKs; Microscopy; microspore embryogenesis; Mitogen-Activated Protein Kinase 1; Mitogen-Activated Protein Kinase 1: metabolism; Mitogen-Activated Protein Kinase 3; Mitogen-Activated Protein Kinase 3: metabolism; Mitogen-Activated Protein Kinases; Mitogen-Activated Protein Kinases: metabolism; Pectins; Pectins: metabolism; Proliferation; Quercus; Quercus: embryology; Quercus: enzymology; Quercus: metabolism; Seeds; Seeds: cytology; Seeds: ultrastructure